(untitled) (Homiletic, 2023)
Preaching becomes true preaching when it is grounded in real place. In real place the pulpit becomes a cross. Among those who have given their voice to preach such a located gospel is Oscar Romero (1917–1980), whose pulpit became a cross when he chose to preach a word not abstracted from his place, but that touched the wounds and sins of his own people. This paper highlights excerpts of Romero’s sermons and commends this preacher as a guide in imagining what “preaching in place” might look like today.